2021
DOI: 10.3390/ijms221910857
|View full text |Cite
|
Sign up to set email alerts
|

In Silico Analysis of Fatty Acid Desaturases Structures in Camelina sativa, and Functional Evaluation of Csafad7 and Csafad8 on Seed Oil Formation and Seed Morphology

Abstract: Fatty acid desaturases add a second bond into a single bond of carbon atoms in fatty acid chains, resulting in an unsaturated bond between the two carbons. They are classified into soluble and membrane-bound desaturases, according to their structure, subcellular location, and function. The orthologous genes in Camelina sativa were identified and analyzed, and a total of 62 desaturase genes were identified. It was revealed that they had the common fatty acid desaturase domain, which has evolved separately, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 145 publications
(206 reference statements)
0
2
0
Order By: Relevance
“…and the seeds of GmFAD3 -silenced plants are larger and heavier in soybean [ 48 ]. The seed weight and oil content of CsaFAD7 and CsaFAD8 transgenic lines are decreased in Arabidopsis thaliana , and the result shows that FAD genes could affect the seed morphology [ 49 ]. Previous studies have shown that cold-tolerant plants contain higher levels of unsaturated fatty acids, and FAD is involved in the cold stress response [ 50 ].…”
Section: Discussionmentioning
confidence: 99%
“…and the seeds of GmFAD3 -silenced plants are larger and heavier in soybean [ 48 ]. The seed weight and oil content of CsaFAD7 and CsaFAD8 transgenic lines are decreased in Arabidopsis thaliana , and the result shows that FAD genes could affect the seed morphology [ 49 ]. Previous studies have shown that cold-tolerant plants contain higher levels of unsaturated fatty acids, and FAD is involved in the cold stress response [ 50 ].…”
Section: Discussionmentioning
confidence: 99%
“…The seed size was measured using 5–10 mg of dry seeds, which were well spread on a plate to observe visible and distinguished individual grains. Next, the seeds were scanned with Unis D6810 (WSeen Detection Technology Co., Ltd, Hangzhou, China), and the seed size was automatically calculated by the SC‐G grain appearance quality image analysis system developed by Hangzhou WSeen Detection Technology Co., Ltd (Raboanatahiry et al., 2021).…”
Section: Methodsmentioning
confidence: 99%